The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1117/1.nph.6.2.025012
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal activity predicts individual differences in optimal attentional strategy for preventing motor performance decline: a functional near-infrared spectroscopy study

Abstract: Directing attention to movement outcomes (external focus; EF), not body movements (internal focus; IF), is a better cognitive strategy for motor performance. However, EF is not effective in some healthy individuals or stroke patients. We aimed to identify the neurological basis reflecting the individual optimal attentional strategy using functional near-infrared spectroscopy. Sixty-four participants (23 healthy young, 23 healthy elderly, and 18 acute stroke) performed a reaching movement task under IF and EF c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 63 publications
(79 reference statements)
4
19
0
Order By: Relevance
“…As shown in other cognitive functions such as motor imagery and focus of attention [ 9 11 , 21 ], we found marked variation in individual WM ability characterized by qualitative dimensions based on the dominance of sensory modality. We also found that the prefrontal activities were significantly correlated with the degree of modality dominance, supporting our hypothesis that the DLPFC and FPC is one of the important regions encoding individual qualitative aspects of the WM system.…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…As shown in other cognitive functions such as motor imagery and focus of attention [ 9 11 , 21 ], we found marked variation in individual WM ability characterized by qualitative dimensions based on the dominance of sensory modality. We also found that the prefrontal activities were significantly correlated with the degree of modality dominance, supporting our hypothesis that the DLPFC and FPC is one of the important regions encoding individual qualitative aspects of the WM system.…”
Section: Discussionsupporting
confidence: 68%
“…1-5) and VD individuals (participant nos. [20][21][22][23][24]. TD individuals did not show large oxy-Hb changes over repeated fNIRS sessions.…”
Section: Task 2: Recording Prefrontal Cortex Using Fnirsmentioning
confidence: 69%
See 3 more Smart Citations